(untitled) (Research, Society and Development, 2024)
The objective of this research was to evaluate the effect of three plastic-mulching films of different colors in the cultivation of mini-tomato in the field. Two experiments were carried out: the first being sown in the summer and the second in the winter. Mini-tomatoes plants with distinct growing habit (determinate and indeterminate) were used and three plastic-mulching film color (black, black/silver, black/white) compared to control (uncovered soil) were tested. The design was in randomized blocks, 2x4 factorial schemes, with four repetitions. Soil temperature, productivity performance and quality of mini-tomatoes were determined. The plastic-mulching films increase the average soil temperature according to the color used. In summer, although small, the black/silver film improves the productive capacity of the mini-tomato with determined growth habit; however, none affects the total soluble solids content. In winter, the black plastic-mulching film favored the soluble solids content of both genotypes and the productivity of the indeterminate. The black plastic-mulching film is suggested as soil cover to produce mini-tomatoes in field conditions during the winter. In summer, low fruit yield quality can makes this technique unfeasible under field conditions.